An Immunohistochemical Study of the Increase in Antioxidant Capacity of Corneal Epithelial Cells by Molecular Hydrogen, Leading to the Suppression of Alkali-Induced Oxidative Stress - Cejka, Cestmir; Kossl, Jan; Holan, Vladimir; Zhang, John H; Cejkova, Jitka (Oxidative medicine and cellular longevity, 2020)
Corneal alkali burns are potentially blinding injuries. Alkali induces oxidative stress in corneas followed by excessive corneal inflammation, neovascularization, and untransparent scar formation. Molecular hydrogen (H2), a potent reactive oxygen species (ROS) scavenger, suppresses oxidative stress and enables corneal healing when applied on the corneal surface. The purpose of this study was to examine whether the H2 pretreatment of healthy corneas evokes a protective effect against corneal alkali-induced oxidative stress. Rabbit eyes were pretreated with a H2 solution or buffer solution, by drops onto the ocular surface, and the corneas were then burned with 0.25 M NaOH. The results obtained with immunohistochemistry and pachymetry showed that in the corneas of H2-pretreated eyes, slight oxidative stress appeared followed by an increased expression of antioxidant enzymes. When these corneas were postburned with alkali, the alkali-induced oxidative stress was suppressed. This was in contrast to postburned buffer-pretreated corneas, where the oxidative stress was strong. These corneas healed with scar formation and neovascularization, whereas corneas of H2-pretreated eyes healed with restoration of transparency in the majority of cases. Corneal neovascularization was strongly suppressed. Our results suggest that the corneal alkali-induced oxidative stress was reduced via the increased antioxidant capacity of corneal cells against reactive oxygen species (ROS). It is further suggested that the ability of H2 to induce the increase in antioxidant cell capacity is important for eye protection against various diseases or external influences associated with ROS production.
Keywords: hojení ran; antioxidancia; zvířata; Female; Oxidative Stress; alkálie; vodík; Alkalies; Corneal Neovascularization; králíci; reaktivní formy kyslíku; Reactive Oxygen Species; Hydrogen; Animals; neovaskularizace rohovky; ženské pohlaví; Epithelial Cells; Wound Healing; oxidační stres; Disease Models, Animal; epitelové buňky; Burns, Chemical; Rabbits; popálení oka; modely nemocí na zvířatech; chemické popálení; Eye Burns; Cornea; Antioxidants; rohovka